Роль модератора у процесі дистанційного навчання - Савченко, Сергій Ігорович; Savchenko, S. I. (Запорізький державний медичний університет, 2021)
У зв’язку із стрімким поширенням коронавірусу COVID-19 в Україні 12 березня 2020 року були введені карантинні заходи, що тривають і сьогодні. Такий тривалий період ізоляції змусив суспільство адаптуватись до нових умов. Відповідні зміни відбулись і в освітній сфері. Швидке тотальне впровадження методів ДО потребувало від викладачів значних зусиль для засвоєння та оволодіння новими засобами забезпечення педагогічного процесу: перш за все, спеціальним програмним забезпеченням – Microsoft Teams, Zoom, Meetup і т.і. [2, c. 35]. Due to the rapid spread of coronavirus COVID-19 in Ukraine on March 12, 2020, quarantine was introduced, which continues today. The long period of isolation required appropriate changes in the field of education. This requires rethinking the role of the moderator in the process of distance education. Materials and methods used are study and generalization of scientific literature on distance education. Given the limited time resources, there is a need to quickly train the minimum required number of teachers from different departments, who will take over the function of moderating the educational process and will provide basic support in the relevant software packages. Distance learning should take a worthy place in the education system of Ukraine, which will facilitate entry into the international educational space. A necessary condition for this is a constant increase in the level of mastery of modern educational software through regular cycles of thematic improvement, seminars, webinars, workshops and more.
The role of the moderator in the process of distance learning
Keywords: distance learning; on-line; moderator